Designing an Optimal Model for Management of Afghan Immigrants in Sistan and Baluchestan Province: Data-based Theorizing Aapproach - Abolfazl Arasteh; Yaser Kahrazeh; Mehdi Salah; Zeinab Hashemi baghi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2023)
IntroductionNot only does Iran have a high emigration flow compared to other countries but also it has a high immigration flow with foreign nationals, such as Afghans and Iraqis, immigrating to the country. The political and social circumstances prevailing in Iran’s Eastern and Western neighbors have led the immigration of their people into Iran, which in turn has extensively directed the national and international attention to policymaking and management of immigrants in Iran. Concerning the policymaking, several principles such as equality, multiple citizenship, dominant or effective citizenship, and human dignity should be taken into consideration by the officials. The issue in Iran manifests itself mostly in the immigration of Afghans, with more than 80% of the immigrant population. The common border as well as linguistic, religious, and cultural commonality between Afghanistan and Iran has provided the ground for the strong presence of Afghan immigrants in Iran, which is generally due to the principle of neighborliness. Sistan and Baluchestan Province is one of Iran’s provinces that are heavily involved with the immigration of Afghans, hosting a large number of legal and illegal Afghan immigrants every year. This widespread immigration has caused various problems and harms concerning security, social, cultural, and economic issues, hence the growing need for an appropriate immigration management model.MethodAs an applied–developmental study, the present article aimed to design an optimal model for management of Afghan nationals in Sistan and Baluchestan Province. The research used the qualitative method and the cross-sectional research design as the data collection procedure. The theoretical experts (university professors) and experimental experts (administrators of Sistan and Baluchestan Province) were considered as the statistical population of the research. Moreover, the theoretical sampling method was used to select the sample, which is an appropriate method for determining the sample size in the grounded theory methodology. A semi-structured interview was used to collect the data. To measure the research validity, the study relied on the criteria of validity, transferability, verifiability, and reliability.The Holsti coefficient was used to evaluate the reliability of the qualitative part. To analyze the collected data, the study employed MaxQDA software to perform the grounded theory method (data-based theory) based on Strauss and Corbin’s approach.To present the research model, the study relied on the viewpoints of eight selected experts and formulated six tentative questions: 1) What are the causal conditions at work in formulating policies for management of Afghan immigrants in Sistan and Baluchestan? 2) What is the central phenomenon in an optimal model for management of Afghan immigrants in Sistan and Baluchestan? 3) What are the influential bases and contexts in the process of formulating the optimal model for management of Afghan immigrants in Sistan and Baluchestan? 4) What strategy should be used to implement the optimal model for management of Afghan immigrants in Sistan and Baluchestan? 5) What are the effective intervening conditions in the process of formulating an optimal model for management of Afghan immigrants  in Sistan and Baluchistan? 6) What are the consequences of implementing the optimal model for management of Afghan immigrants in Sistan and Baluchestan?ResultsHaving analyzed the results of the interviews by using the database method, the research obtained the main indicators and categories as follows: background conditions (main category: implementation of conditional ban in the province), causal conditions (main categories: full implementation of the law prohibiting the presence of foreign nationals; cultural, religious and political similarities; and establishment of centralized management), the central phenomenon (main category: management of Afghan immigrants), strategies and actions (main category: the amendment of law and legislation), intervening conditions (main category: condemnation of the policy on banning the presence of foreign nationals), consequences (main categories: crime reduction and development of sustainable security in the province, improvement of economic conditions in the province, increase in the people’s level of satisfaction).Discussion and ConclusionConcerning the main indicators and categories mentioned above, the full implementation of the law prohibiting the presence of foreign nationals; cultural, religious, and political similarities; and establishment of centralized management were considered as the basic factors affecting the management of Afghan immigrants. This specific method of management effects the strategic amendment of laws and legislation. Yet it should be taken into account that condemnation of the policy on banning the presence of foreign nationals acts as an intervening factor in this respect, and the implementation of a conditional ban in the province can provide the background conditions. The strategic amendment of laws will bring about the behavioral consequences such as crime reduction and development of sustainable security in the province, improvement of economic conditions in the province, and increase in the people’s level of satisfaction. The results also showed that condemnation of the policy on banning the presence of foreign nationals is a deterrent and intervening factor with negative effects on management of Afghan immigrants in Sistan and Baluchestan, so it is necessary to eliminate it by adopting appropriate strategies.